Liguleless narrow and narrow odd dwarf act in overlapping pathways to regulate maize development and metabolism. (11th October 2022) - Abraham‐Juárez, María Jazmín; Busche, Michael; Anderson, Alyssa A.; Lunde, China; Winders, Jeremy; Christensen, Shawn A.; Hunter, Charles T.; Hake, Sarah; Brunkard, Jacob O.
SUMMARY: Narrow odd dwarf ( nod ) and Liguleless narrow ( Lgn ) are pleiotropic maize mutants that both encode plasma membrane proteins, cause similar developmental patterning defects, and constitutively induce stress signaling pathways. To investigate how these mutants coordinate maize development and physiology, we screened for protein interactors of NOD by affinity purification. LGN was identified by this screen as a strong candidate interactor, and we confirmed the NOD‐LGN molecular interaction through orthogonal experiments. We further demonstrated that LGN, a receptor‐like kinase, can phosphorylate NOD in vitro, hinting that they could act in intersecting signal transduction pathways. To test this hypothesis, we generated Lgn‐R;nod mutants in two backgrounds (B73 and A619), and found that these mutations enhance each other, causing more severe developmental defects than either single mutation on its own, with phenotypes including very narrow leaves, increased tillering, and failure of the main shoot. Transcriptomic and metabolomic analyses of the single and double mutants in the two genetic backgrounds revealed widespread induction of pathogen defense genes and a shift in resource allocation away from primary metabolism in favor of specialized metabolism. These effects were similar in each single mutant and heightened in the double mutant, leading us to conclude that NOD and LGN act cumulatively in overlapping signaling pathways to coordinate growth‐defense tradeoffs in maize. Significance Statement: Narrow odd dwarf ( nod ) and Liguleless narrow ( Lgn ) are pleiotropic maize mutants that severely disrupt growth and development. Here, we share our unexpected discovery that the NOD and LGN proteins physically interact at the plasma membrane. Using a combination of genetics, functional genomics and metabolomics, we then show that nod and Lgn impact overlapping stress–response and developmental patterning pathways in maize.